Defense Diplomacy of Middle Powers in Digital International Relations - Hanggarini, Peni (Andalas Journal of International Studies (AJIS), 2025)
In an era of rapid digital innovation and the rise of artificial intelligence (AI), growing technological power imbalances have generated serious concerns about the equality, agency, and sovereignty of state and non-state actors. This study uses a qualitative, interpretivist methodology to examine the consequences of the digital divide. It focuses on how middle powers manage technological competition while maintaining strategic autonomy in the transformation of international relations. The findings indicate that while digital technology and AI enhance state capabilities and reshape global power hierarchies, they generate critical, ethical, and political challenges, particularly around surveillance, accountability, and algorithmic bias. This study argues that middle power can use defense diplomacy as a strategic instrument to confront the challenges of digital technology. Defense diplomacy employs comprehensive approaches, both coercive and non-coercive, and serves as an effective strategy for middle powers to influence global norms, develop cooperative security frameworks, and manage technological disruptions through building trust among actors. Ultimately, this study contributes to the interdisciplinary discourse on digital international relations by offering a framework for middle powers in an era increasingly shaped by algorithmic decision-making and cyber politics.